IMPLEMENTATION OF DIFFERENTIATED LEARNING TO ENHANCE CRITICAL THINKING SKILLS IN ELEMENTARY SCHOOL STUDENTS (INTERNATIONAL SEMINAR, 2024)
Thisㅤresearchㅤaimsㅤtoㅤdevelop and implementㅤa differentiated learningㅤmodel to enhance critical thinking skills amongㅤelementaryㅤschoolㅤstudents. Theㅤmethodㅤusedㅤinㅤthis study is Research and Development (R&D), which consists of the stages of needs analysis, learning model design, trials, and evaluation.ㅤTheㅤdifferentiatedㅤlearningㅤmodelㅤwasㅤdeveloped byㅤconsideringㅤdifferencesㅤin students' learning styles,ㅤabilities, andㅤinterests, which is expected to encourage students to think moreㅤcriticallyㅤwhenㅤsolvingㅤproblems.ㅤTheㅤresearchㅤresults show that the implementation ofㅤdifferentiatedㅤlearningㅤcan enhance students'ㅤcriticalㅤthinkingㅤskills, as evidenced by the increase inㅤcriticalㅤthinking test scores and positive responses from students towards the conducted learning. Based on these findings, differentiated learning can be an effective alternative inㅤdevelopingㅤcriticalㅤthinkingㅤskillsㅤinㅤelementaryㅤschoolstudents. This study also suggests that teachers pay more attention to the diversity of student characteristics in designing and implementing lessons.